Role of Precise Rehabilitation in Diagnosis and Treatment of Consciousness Disorder Caused by Severe Craniocerebral Injury - Yi WU (康复学报)
Severe craniocerebral injury is the leading cause of death and disability. Traumatic brain injury can lead to a variety of dysfunctions, the most serious of which is disturbance of consciousness (DOC). The establishment of precise diagnosis and accurate treatment for DOC patients is a major goal in the development of accurate rehabilitation and a prerequisite for clinical improvement for patients with dysfunction. As the clinical arousing strategy is not yet perfect, more effective evidences are needed, and the standardized treatment, sorting and chronic care for DOC patients have to be more effectively carried out. Nonetheless, several treatments have been utilized with contrasting results, such as pharmacological intervention, peripheral nerve electrical stimulation, central nervous stimulation, transcranial magnetic stimulation, hyperbaric oxygen therapy and cell transplantation. The purpose of this article is to introduce the features of various diagnostic and arousal techniques and to guide the rehabilitation of DOC in early clinical practice. However, traumatic injury is a highly individualized process, of which damage relys on a variety of factors and thus the individual differences also affect the therapeutic effect of arousing measures. Therefore, it is necessary to establish accurate and individualized diagnosis programs and treatment process for DOC patients.